How psychology teachers assess scientific reasoning: a study of assessment criteria and epistemological beliefs - Marleen Evers; J. Elen; M. Vandecandelaere (Cogent Education)
Psychology education presents challenges for both teachers and students due to its complex and multi-perspective nature. Fostering scientific reasoning and argumentation (SRA) in psychology is an important goal in secondary education and can help students navigate this complexity. However, existing research falls short of guiding teachers on how to teach SRA skills. This study looks at one aspect of this teaching practice, specifically the evaluation of SRA, and explores its relationship to teachers’ epistemological beliefs. We asked 31 psychology teachers from Belgium (Flanders) and the Democratic Republic of Congo to formulate assessment criteria and evaluate student responses using prompted criteria. The analysis revealed a focus on process and argumentation criteria, with difficulties in identifying and applying the epistemic criteria central to assessing SRA. Also, while the prompted criteria increased attention to argumentation quality, they did not ensure an accurate approach to SRA tasks, often reframing them as application or analysis tasks, nor an accurate use of epistemic criteria to assess the task. Teachers’ epistemological profiles were not reflected in their criteria, nor in their use of prompted criteria. The findings suggest a need for more in-depth research into teachers’ epistemic understanding of psychology as a scientific discipline.